2018
DOI: 10.1111/ijfs.13952
|View full text |Cite
|
Sign up to set email alerts
|

Amounts of malondialdehyde do not accurately represent the real oxidative level of all vegetable oils: a kinetic study of malondialdehyde formation

Abstract: Summary Malondialdehyde (MDA), a widely used oxidation indicator for both lipid and edible oil, has been suggested to be genotoxic and cytotoxic, thus attracting increasing attentions about its formation and exposure assessment. In this study, kinetics of MDA formation in vegetable oils and model oils were investigated by high‐performance liquid chromatography. Results showed MDA contents firstly increased rapidly then kept to a plateau over time in both reaction systems at 100, 140 and 180 °C, significant tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
(52 reference statements)
2
21
0
Order By: Relevance
“…As expected, MDA content showed significant correlation with PUFA content and other oxidation indicators, including POV, AV, CDV, and p‐AV in CO, RO, and LO ( P < 0.05). But MDA content showed a relatively low correlation ( P > 0.05) with POV in PO (0.702) and CLO (0.732), disqualifying MDA as a suitable candidate to evaluate the oxidation of vegetable oils with low PUFA content, which was in accordance with our previous report that MDA could not reflect the oxidation of all the vegetable oils, such as PO and CLO, which contain low PUFA. While HHE content showed significant correlation ( P < 0.05) with the traditional oxidation indicators, particularly with the ω‐3 fatty acid.…”
Section: Resultssupporting
confidence: 89%
“…As expected, MDA content showed significant correlation with PUFA content and other oxidation indicators, including POV, AV, CDV, and p‐AV in CO, RO, and LO ( P < 0.05). But MDA content showed a relatively low correlation ( P > 0.05) with POV in PO (0.702) and CLO (0.732), disqualifying MDA as a suitable candidate to evaluate the oxidation of vegetable oils with low PUFA content, which was in accordance with our previous report that MDA could not reflect the oxidation of all the vegetable oils, such as PO and CLO, which contain low PUFA. While HHE content showed significant correlation ( P < 0.05) with the traditional oxidation indicators, particularly with the ω‐3 fatty acid.…”
Section: Resultssupporting
confidence: 89%
“…The levels of MDA also varied in different oils; the highest was observed in the LO, and the lowest was in the CO. This is probably because linolenic acid (ω‐3) was the strong precursor of MDA in the LO in which it was found to be most abundant, but it was a relatively weak one in the CO in which it was also found (Ayala et al , ; Ma et al , ). The MDA levels in the CO used for the FF frying group were significantly ( P < 0.05) higher than those in the CO used for the FCBM frying group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Guillén & Uriarte () observed high levels of HHE and HNE in sunflower and linseed oils after prolonged heating at frying temperatures. Ma et al () investigated the formation kinetics of MDA during thermal processing at 100–180 °C. LaFond et al () studied the formation of HNE during frying but not its levels in potato sticks.…”
Section: Introductionmentioning
confidence: 99%
“…It had been reported that the tocopherols in vegetable oils might influence the rate constant (Ma et al ., ), but in our experiment the tocopherols were stripped prior to the heating experiment. Therefore, differences among rate constants were due to differences between oil types.…”
Section: Resultsmentioning
confidence: 99%
“…The tocopherol contents of vegetable oils vary, which can affect kinetic parameters (Farhoosh et al, 2008). Our group found that tocopherol affected the rate constant of MDA formation in different oils (Ma et al, 2019). To eliminate the influence of tocopherol and obtain kinetic and thermodynamic data for HHE and HNE formation influenced only by the type of vegetable oil used, the tocopherols were stripped from the oils prior to heating on an alumina column based on a previous report (Fuster et al, 1998).…”
Section: Purification Of Vegetable Oilsmentioning
confidence: 99%